Role of the digital economy in the sphere of tourism in the Republic of Uzbekistan - Bakaev Ziyovuddinkhon Toshbolta ugli (Proceedings of The ICECRS, 2020)
Digitalization of the economy has an impact on all spheres of society and human life, the tourism industry is no exception. The article examines the main directions of the influence of the digital economy on the tourism industry and considers the main technologies that affect the digital transformation of the tourism industry.